Strategies of Green Transformation in Production Operation of Power Battery Enterprises Under the Dual- Carbon Target - Zhang Shuai; Purwanto Purwanto (Asia Pacific Journal of Management and Education (APJME), 2026)
Following the Paris Climate Agreement, global efforts to reduce carbon emissions have shifted from policy commitments to practical implementation. Electricity generation and transportation remain two of the largest sources of carbon emissions. Although new energy vehicles (NEVs) contribute to the decarbonization of the transportation sector, the production of power batteries continues to generate substantial emissions. This study examines the green transformation strategy of CATL under China's "dual-carbon" targets. As a global leader in the power battery industry and the first company in the sector to introduce a carbon neutrality plan, CATL provides a valuable case for analysis. Using a literature review and case study approach, this research explores the company's transformation through green corporate culture, management practices, and production processes. The findings indicate that CATL has successfully reduced carbon intensity, improved energy efficiency, increased the use of recycled materials, and strengthened supply chain resilience